(untitled) (Research, Society and Development, 2024)
Entrepreneurship is essential for society, as it deals with problems related to it. For such problems, potential solutions are raised that allow for solving problems in a better way than the existing ones. Companies need to constantly undertake in order to stay alive in the modern competitive society. In the context of micro and small enterprises (MSE), undertaking is also necessary, but this is an even more arduous activity. After all, this category of companies faces several challenges in our country, such as lack of financial resources, difficulties in managing cash flow and time, low access to credit, etc. Considering this reality, SEBRAE presents itself as an important actor in society to support MSE in this journey. One example is the Local Innovation Agents (ALI) Digital Transformation program, which supports companies in the use of technologies. This work aims to identify factors that influence MSEs in the adoption of technologies to improve their businesses. Understanding the challenges and difficulties faced by micro and small entrepreneurs is essential to be able to better apply the energy and resources of their actions. To this end, a qualitative analysis was conducted of the perception of ALI who worked in different companies and closely observed the nuances of implementing new technologies. The results highlight the importance and difficulties of using technologies by MSE, but also provide contributions on how a support program for micro and small entrepreneurs can be adjusted to leverage the expected results.